Hegemonial Evaluation of Importance of Women Education and their Socio Economic Development in Fika Local Government Area , Yobe State, Nigeria - Baba, Umar Saleh; Anumaka, Blessing Ijeoma (Advances in Social Sciences Research Journal, 2019)
The paper discussed the importance of women education and the socio economic development in Fika local government area of Yobe state, Nigeria. The paper focused on the concept of women education, the concept of socio-economic development and the importance of women education in socio-economic development. This study employed quantitative approach with descriptive correlation design and also the total population of 66901 and the sample size of 382 respondents while questionnaire and interview guide were used as research instruments to collect required data.The study also used sample of 382 respondents, frequency and percentage techniques, means and standard deviation and finally, Pearson linear correlation co-efficient (PLCC) to establish the relationship between women education and the element of socio economic development in Fika local government area of Yobe state. The findings of this study revealed that there is positive and very significant relationship between women education and their household income level, and a positive relationship exist with standard of living, economic development and women education but this is not significant. The recommendation of this study is that all effort to empower women should be directed toward educational empowerment in the state as this is significant to overall economic growth in the state. This is because women education in terms of socio-economic development have significant effect on their family,social and economic development of a nation as a whole..